Markers of hydration status - Shirreffs, S. M. (The Journal of Sports Medicine and Physical Fitness, 2000)
This paper reviews the literature, describes and discusses methods by which whole body hydration status can be determined in humans. A method of determining whether or not an individual is hypohydrated is of particular significance in an exercise situation as even moderate levels of hypohydration have a negative impact on exercise performance. Inspection of the published literature indicates that a number of methods have been used to determine hydration status. Body mass changes, urinary indices (volume, colour, protein content, specific gravity and osmolality), blood borne indices (haemoglobin concentration, haematocrit, plasma osmolality and sodium concentration, plasma testosterone, adrenaline, noradrenaline, cortisol and atrial natiuretic peptide), bioelectrical impedance analysis, and pulse rate and systolic blood pressure response to postural change are discussed. The urinary measures of colour, specific gravity and osmolality are more sensitive at indicating moderate levels of hypohydration than are blood measurements of hematocrit and serum osmolality and sodium concentration. Currently no "gold standard" hydration status marker exists, particularly for the relatively moderate levels of hypohydration that frequently occur in an exercise situation. The choice of marker for any particular situation will be influenced by the sensitivity and accuracy with which hydration status needs to be established together with the technical and time requirements and expense involved.